The Role of Information and Communication Technology (ICT) in Managing Post Harvest Losses in Tomato Production in Adamawa State, Nigeria - Mohammed Aliyu, Abubakar; Isa Mamza, Shamsuddeen; Usman Pariya, Ibrahim; Tahir Gidado, Marbiyat (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
In Nigeria today, particularly in Adamawa State, tomato production continuously faces significant challenges of post-harvest losses, affecting the farmers and tomato sellers and the consumer. This study explores how Information and Communication Technology (ICT) can effectively manage these losses. Through utilizing ICT tools and technologies such as weather forecasting applications, real-time market information, and other ICT aided processing and storage techniques, farmers can make informed decisions throughout the production and distribution process. These technologies empower farmers to adopt best practices in handling their produce, improve storage conditions, and access timely market information, thereby reducing losses and increasing profitability. However, challenges such as access to technology, infrastructure, and digital literacy remain critical barriers. Addressing these issues is essential for maximizing the potential of ICT in transforming tomato production in Adamawa State, to ensure a sustainable agricultural practices and economic growth in the Adamawa and Nigeria as a whole.